PENGARUH SIKAP TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP NEGERI 23 MERANGIN - Asmarani, Dian (STKIP YPM Bangko, 2017)
This study aims to determine the relationship and the influence of attitudes toward learning outcomes in mathematics. This study uses a quantitative approach with a correlational method that connects two variables, namely the variable learning attitudes as independent variables and mathematics learning outcomes as the dependent variable. The population in this study were class VII students of SMP Negeri 23 Merangin, totaling 102 people. Sampling uses simple random sampling technique by drawing. Determination of sample size using the Taro Yamane formula with a sample size of 51 respondents. Learning attitude data collection uses a Likert scale questionnaire with 4 answer choices, and documentation techniques for learning outcomes data. Before being analyzed the transformation of learning attitude data, data normality test using Kolmogorov-Smirnof, linearity using theF formulacalculated, and hypothesis testing using Pearson Product Moment correlation, significance (Z-test), determination coefficient (KP), simple linear regression equation, and regression significance test. Based on the test requirements analysis, stated data on learning attitudes and learning outcomes are normally distributed and linear. The results of data analysis using the Pearson Product Moment (PPM) formula. From the formula, it is known that the correlation coefficient is 0.375 and the rvalue istable 0.281, so that it can be expressed rcount ˃ rtable or 0.375> 0.281. This means that H0 is rejected and Ha is accepted. Furthermore, for the significance of the Z-test it produces a value of 2.67 at the significance level of 5% and dk = 49 obtained by Ztable of 1.96. Because Zcount ˃ Ztable or 2.67> 1.96 means that there is a significant effect with a large contribution (coefficient of determination) 14.06% and a simple linear regression equation ŷ = 58,698 + 0.265X. So that it can be concluded that there is a significant influence between learning attitudes towards the learning outcomes of mathematics in class VII students of SMP Negeri 23 Merangin.